School Coexistence in Spain: Current Challenges and Opportunities for Improvement through Good Practices - Alonso de Castro, María Goretti (Avances en Supervisión Educativa, 2025)
School coexistence is a fundamental pillar for the development of safe, inclusive and respectful educational environments. In Spain, both the Ministry of Education and Vocational Training and the regional administrations have promoted various strategies to improve coexistence in educational centers. This article analyzes national and regional regulations, government initiatives and teacher training programs aimed at preventing bullying and peaceful conflict resolution. Strategies for more effective and unified management are also proposed, highlighting the key role of educational inspection in monitoring and improving school coexistence as well as examples of good practice projects that can serve as inspiration. Finally, Current challenges are examined, such as inequality in the implementation of policies, the lack of specialized resources and the need for greater coordination between administrations, centers and families. These limitations underline the need for more inclusive and precise strategies to maximize the impact of indicators on education.
Keywords: School coexistence, Educational regulations, Educational inspection, European projects, Erasmus